Patient Acceptance of Teleurology via Telephone vs Face‐to‐Face Clinic Visits for Hematuria Consultation at a Veterans Affairs Medical Center. Issue 4 (July 2018) - Safir, Ilan J.; Zholudev, Vitaly; Laganosky, Dean; Aliperti, Louis; Al‐Qassab, Usama; Lindelow, Jennifer; Filson, Christopher P.; Issa, Muta M.
Abstract : Introduction : We evaluated the experience and preferences of patients undergoing hematuria consultation via teleurology compared to a conventional face‐to‐face clinic visit. Methods : Patients evaluated for hematuria with teleurology or face‐to‐face clinic visit were surveyed regarding their experience and preferences. The survey consisted of 27 questions evaluating overall acceptance and satisfaction (8 questions), impact factors (17) and preference (2). Results : A total of 450 patients participated in the survey at a 2‐to‐1 ratio (300 via teleurology, 150 via face‐to‐face visits). Overall, patient satisfaction level was higher with teleurology compared to face‐to‐face clinic visits (mean score 9.2 vs 8.4, p < 0.0001). This finding was observed in all 8 domains (acceptance, efficiency, convenience, friendliness, quality of interview, communication and care, provider professionalism and privacy protection, all p <0.001). Transportation related issues were the most common underlying reason that influenced patient opinion, with at least 1 transportation factor being reported by 280 of 300 teleurology patients (93.3%) and 133 of 150 patients seen face‐to‐face (88.7%). Clinic operation and provider interaction factors similarly impacted patient satisfaction and preference. Time to access was significantly better for teleurology (12 days) compared to face‐to‐face clinics (72 days, p < 0.001). Overall incidence of bladder cancer was 5.6% (25 of 450 patients), which was observed in 6.3% of the teleurology group (19 of 300) and 4.0% of the face‐to‐face group (6 of 150, p = 0.386). Conclusions : Patients prefer teleurology to face‐to‐face clinic visits for the initial evaluation of hematuria. Teleurology positively impacts compliance and access by potentially eliminating common challenges facing patients, and by improving efficiency, convenience and flexibility.